Chemi-resistive response of rutile titania nano-particles towards isopropanol and formaldehyde: a correlation with the volatility and chemical reactivity of vapors. (24th January 2017) - Das, P; Mondal, B; Mukherjee, K
Abstract: The performance of phase pure rutile titania nano-particles for gas/vapor sensing is not well explored in open literature, mostly because of their moderate chemical activity. However, the high thermal stability of rutile titania could be beneficial towards making a stable chemi-resistive sensor, operable generally at higher temperature. Herein, we have investigated the chemi-resistive response characteristics of rutile phase titania nano-particles for the detection of isopropanol and formaldehyde vapors. Titania nano-particles are synthesized through a hydrothermal route and characterized in terms of their phase formation behavior and micro-structural features. The sensing characteristics of the particles are measured by varying the operating temperature (275 °C–350 °C) of the sensor and concentrations (20–200 ppm) of the vapors, using a static flow gas sensing measurement set-up. The rutile titania particles are found more responsive towards isopropanol than formaldehyde. An attempt is made here to correlate the sensing performance of titania sensors with the volatility and chemical reactivity of studied vapors. The higher response of the sensor towards isopropanol is predicted, due to its comparatively lower volatility and more suitable chemical structure for oxidation on the sensor surface.